ANALISIS KEUNTUNGAN USAHATANI DAN PELUANG PENGEMBANGAN DIVERSIFIKASI PANGAN POKOK SUMBER KARBOHIDRAT DI KABUPATEN KEPAHIANG - Asriani, Putri Suci; Irnad, Irnad; Badrudin, Redy (Jurnal AGRISEP, 2013)
Cassava, maize, and sweet potato are staple foods source diversification alternatives which are quite popular in society. But in terms of the efficiency of farming, it is still needed to study which farm remains profitable and has diversification opportunity to be developed as staple food and sources of carbohydrates that can be aligned with the rice. Based on this research, it is known that a variety of food sources of carbohydrates that have a good potential for development, in order are cassava, sweet potato, and corn. In addition, all of the alternative staple foods also have the ability to profit creation higher than lowland rice. Some strategies for developing in diversification staple food source of carbohydrates can be arranged in this study, such as: (1) increasing the number and the quality of production followed by improvement of processing subsystems, network access market, supporting institutions and empowerment, (2) revitalizing structured farming training and extension in order to accelerate the transformation of technology and government support in the form of agricultural development policies, (3) strengthening the bargaining position of farmers through increasing access to information and a guaranteed market, and (4) developing infrastructure to improve productivity and competitiveness of farmers, as well as optimization economic institutions/cooperatives.